Digital Literacy Learning Through School TV In PAUD - Tutin Rahayu; Robby Nofrianto; Angel Nathania Sunarto; Annisa Hakim; Sri Watini (Politeknik Siber Cerdika Internasional, 2023)
Digitalization of early childhood education has targeted learning media. Palform TV Sekolah is present as an alternative to digital-based learning media. This study aims to explore the potential use of TV School media as a medium in increasing digital literacy in early childhood at PAUD Cinta Kasih Ibu Cengkareng Timur, West Jakarta. The research method used is a qualitative description involving 18 early childhood children in PAUD Cinta Kasih Ibu with 6 girls and 12 boys. Data collection techniques used in this study are through observation, interviews and documentation. The research findings show that the use of TV media can increase digital literacy in early childhood. Children demonstrate an increased understanding of the use of technology and electronic media, and their ability to access, evaluate and use information effectively.